Mapping the wine visit experience for tourist excitement and cultural experience - Santos, V. R.; Dias, Á.; Ramos, P.; Madeira, A.; Sousa, B. (Annals of Leisure Research, 2023)
This study aims to examine and estimate the relationships between wine involvement, cultural experience, winescape attributes, wine excitement and sensorial attraction in two different wine tourism destinations and the antecedent role of wine involvement as the starting point that enhances the other dimensions. Survey data was analysed using structural equation modelling. Results reveal a direct relationship of wine involvement, winescape attributes, and sensorial attraction in the cultural experience and wine excitement of wine tourists. Furthermore, the mediating role of winescape attributes and sensorial attraction was identified in the relationship between wine involvement cultural experiences. These results allow wine marketeers and decision-makers to map the different stages in a wine tourism experience and to combine the use of these five different wine tourism dimensions to deliver a superior cultural experience.